An action research on using body language in teaching English to 5-year-old children at Sao Mai Kindergarten = nghiên cứu hành động về dạy tiếng Anh cho trẻ 5 tuổi qua ngôn ngữ cử chỉ tại Trường mầm non Sao Mai .M.A. Thesis Linguisitcs: 60 14 01 11 - Đỗ, Thu Hương (ĐHNN, 2017)
42p. + CD-ROM